2012
DOI: 10.1038/onc.2011.613
|View full text |Cite
|
Sign up to set email alerts
|

A transcriptional variant of the LC3A gene is involved in autophagy and frequently inactivated in human cancers

Abstract: Microtubule-associated protein 1 light chain 3 has an important role in autophagy. The human LC3 gene family has five members, LC3A (variant-1: v1 and -2: v2), LC3B, LC3B2 and LC3C. Although a form of LC3B modified by phosphatidylethanolamine (form-II) is localized in autophagosomes, it is not clear whether other LC3 proteins also function in autophagy. Here, we examined the association between autophagy and human LC3 proteins during starvation-or p53-induced autophagy in Saos-2 cells. In an analysis of the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
66
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 40 publications
5
66
0
Order By: Relevance
“…While LC3B has been known as the major LC3 in the autophagosome, a recent study demonstrated that the other LC3 family member LC3A-vareint1 can also mediate autophagosome formation as efficiently as LC3B [26]. Contrary to LC3B regulation, Raf activation significantly decreased LC3A-vareint1 mRNA levels (Fig.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…While LC3B has been known as the major LC3 in the autophagosome, a recent study demonstrated that the other LC3 family member LC3A-vareint1 can also mediate autophagosome formation as efficiently as LC3B [26]. Contrary to LC3B regulation, Raf activation significantly decreased LC3A-vareint1 mRNA levels (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…We determined the effect of Raf/MEK/ERK activation on LC3B, a major LC3 in the autophagosome [26], and SQSTM1 in different cell types, including the human prostate cancer line LNCaP, immortalized human kidney epithelial cell line HEK293, primary cultured normal foreskin fibroblast BJ, and immortalized lung fibroblast IMR90E1A, which have been used as models to study the mechanisms underlying cellular responses to aberrant Raf/MEK/ERK activation [6,18,27]. To specifically control the pathway activity, we used the tamoxifen-regulated ΔRaf-1:ER, a CR3 catalytic domain of Raf-1 fused to hormone binding domain of the estrogen receptor [28].…”
Section: Resultsmentioning
confidence: 99%
“…The core molecular machinery required for the formation of an autophagosome comprises a heterogeneous group of proteins encoded by autophagy-related ATG genes, such as ATG5, Beclin1 (also known as ATG6), and microtubule-associated protein 1 light chain 3 (LC3), a human homolog of yeast ATG8. [10][11][12] The conversion of cytosolic LC3-I to autophagosome-bound LC3-II acts as a biochemical marker of active autophagy, [10][11][12][13][14][15][16] and it has been increasingly appreciated that the immunohistochemical detection of cytoplasmic LC3 puncta in formalin-fixed, paraffinembedded specimens (FFPE) correlates with the amount of autophagosomes or autophagolysosomes. 14,17,18 Although it is known that cancer cells with Ras mutations are addicted to upregulated autophagic flux, 10,11,13,14 little has been done to clarify the role of autophagy in EGFR-driven carcinoma cells.…”
mentioning
confidence: 99%
“…Recently, Bai et al found that the function of GFP-LC3Av1 (a LC3A variant) was similar to GFP-LC3B during the process of autophagy. In the further study, LC3Av1 was shown to be frequently methylated in ESCC and the restoration of LC3Av1 expression exerted its anti-proliferative activity in vivo [20]. The expression of autophagy-related protein Beclin 1 was significantly downregulated in breast tumors due to aberrant promoter methylation [21].…”
Section: Epigenetic Control and Autophagy In Cancermentioning
confidence: 97%